2018
DOI: 10.1111/zsc.12331
|View full text |Cite
|
Sign up to set email alerts
|

A new surface gliding species of Chironomidae: An independent invasion of marine environments and its evolutionary implications

Abstract: Insects have invaded marine habitats only rarely and secondarily. Recently, we discovered a flightless dipteran species skating rapidly on the surface of seawater ponds at the Pacific coast of eastern China. Morphological analyses initially suggested an isolated position of the non‐biting midge, suggesting the erection of a new genus within Chironomini (Diptera: Chironomidae). However, an analysis of molecular data revealed that the marine species is in fact nested within the species‐rich genus Dicrotendipes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…WoRMS contains an ongoing list of marine dipterans, but relies entirely upon published literature and the scientific community to self‐report ecological descriptions of species. Some groups with well‐known marine life history such as Thoracochaeta (Sphaeroceridae: Limosiinae; (Marshall, 1982 ; Hodge et al., 2017 )), Oedoparena (Dryomyzidae; (Gibson & Choong, 2021 )), Telmatogeton (Chironomidae: Telmatogetoninae; (Brodin & Andersson, 2009 ; Lorenz Simões et al., 2020 ; Nondula et al., 2004 )), Thalassomya (Chironomidae: Telmatogetoninae; (Qi et al., 2019 )), and Tanytarsus (Qi et al., 2019 ) were missing from the overall list of marine species in WoRMS. Similarly, genera like Fucellia (Anthomyiidae: Anthomyiinae; (Kaczorowska, 2005 )) and Pontomyia (Chironomidae: Chironominae; (Huang & Cheng, 2011 )) were given marine designations in WoRMS as a family but were not among the taxa examined in the fly tree of life (Wiegmann et al., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…WoRMS contains an ongoing list of marine dipterans, but relies entirely upon published literature and the scientific community to self‐report ecological descriptions of species. Some groups with well‐known marine life history such as Thoracochaeta (Sphaeroceridae: Limosiinae; (Marshall, 1982 ; Hodge et al., 2017 )), Oedoparena (Dryomyzidae; (Gibson & Choong, 2021 )), Telmatogeton (Chironomidae: Telmatogetoninae; (Brodin & Andersson, 2009 ; Lorenz Simões et al., 2020 ; Nondula et al., 2004 )), Thalassomya (Chironomidae: Telmatogetoninae; (Qi et al., 2019 )), and Tanytarsus (Qi et al., 2019 ) were missing from the overall list of marine species in WoRMS. Similarly, genera like Fucellia (Anthomyiidae: Anthomyiinae; (Kaczorowska, 2005 )) and Pontomyia (Chironomidae: Chironominae; (Huang & Cheng, 2011 )) were given marine designations in WoRMS as a family but were not among the taxa examined in the fly tree of life (Wiegmann et al., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The case is not unique in Chironomidae: the marine species Dicrotendipes sinicus Qi & Lin was suggested as a new genus within the subfamily Chironominae. However, the analysis of genetic data revealed that the marine species nested within the genus Dicrotendipes (Qi et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the rather unusual combination of the morphological characters of the adult males of the species indicates that they might have been surface-skimmers, as are a number of extant representatives of Chironomidae (Qi et al, 2018). Prominent characters of H. noncatafractata that point towards a surface skimming lifestyle include shortened antennae, robust and widened legs (especially femora) and relatively short wings.…”
Section: Palaeoecological Implications Of the Culicomorphan Diversity In The Kishenehn Formationmentioning
confidence: 97%
“…These traits are exhibited by midges inhabiting the intertidal zone of the seas or living as a surface skater in hypersaline habitats (Armitage et al, 1995;Qi et al, 2018) with salinities up to 40‰ (Armitage et al, 1995;Qi et al, 2018;Shadrin et al, 2019). In the new species, these traits are less developed than in the known intertidal and marine representatives of Chironomidae, i.e., Pontomyia spp., Clunio spp., Dicrotendipes sinicus Qi and Lin, 2018 and Baeotendipes noctivagus Kieffer, 1911(Qi et al, 2018. It is therefore probable that this combination of traits indicates that adults of H. noncatafractata sp.…”
Section: Systematic Palaeontologymentioning
confidence: 98%